Ex-Vivo Skin Explant Culture Is a Model for TSLP-Mediated Skin Barrier Immunity - Thomas Bauer; Daniela Gubi; Jörg Klufa; Philipp Novoszel; Martin Holcmann; Maria Sibilia (Life, 2021)
The skin is the outermost barrier protecting the body from pathogenic invasion and environmental insults. Its breakdown initiates the start of skin inflammation. The epidermal growth factor (EGFR) on keratinocytes protects this barrier, and its dysfunction leads to atopic dermatitis-like skin disease. One of the initial cytokines expressed upon skin barrier breach and during atopic dermatitis is TSLP. Here, we describe the expression and secretion of TSLP during EGFR inhibition and present an ex-vivo model, which mimics the early events after barrier insult. Skin explants floated on culture medium at 32 °C released TSLP in parallel to the activation of the resident Langerhans cell network. We could further show the up-regulation and activation of the AP-1 family of transcription factors during atopic-like skin inflammation and its involvement in TSLP production from the skin explant cultures. Inhibition of the c-Jun N-terminal kinase pathway led to a dose-dependent blunting of TSLP release. These data indicate the involvement of AP-1 during the early stages of atopic-like skin inflammation and highlight a novel therapeutic approach by targeting it. Therefore, skin explant cultures mimic the early events during skin barrier immunity and provide a suitable model to test therapeutic intervention.